A meta-analysis of genome-wide association studies identifies multiple longevity genes - Joris Deelen (Nature Portfolio, 2019)
Genome-wide association studies have only revealed a handful of genetic loci for longevity. Here, in a case–control design based on phenotype definitions of individuals surviving at or beyond the age corresponding to the 90th and 99th survival percentile, the authors report two additional loci located in the APOE locus and near GPR78.